Studies on Adult Longevity of Callosobruchus chinensis (L.) Developing in Different Pulses - Neog, Pankaj (International Journal of Bio-resource and Stress Management, 2023)
Adult longevity for mated and unmated individuals of Callosobruchus chinensis L. (both male and female) was studied separately with adults emerging from nine different pulses at both controlled temperature (28+2°C) and room temperature (23.8-31.5°C) in the laboratory. Further, the longevity for mated females was also studied separately providing food for oviposition and without providing food for oviposition. At both controlled and room temperature, the males developing in green gram and chickpea (deshi) had the longest average longevity (11.83 and 11.33 days, respectively), while the males developing in soybean had the shortest average longevity (7.50 and 7.00 days, respectively). Similarly, at both controlled and room temperature, the females developing in green gram and chickpea (deshi) had the longest average longevity (10.00 and 9.56 days, respectively), while the females developing in soybean had the shortest average longevity (6.56 and 6.11 days, respectively). The unmated males lived longer (avg. 11.24 days) than mated ones (avg. 8.79 days). The longevity for mated female increased when they were provided food for oviposition as compared to those without providing food for oviposition. The unmated females lived longer (avg. 9.83 days) than mated females with food and without food (avg. 8.04 and 7.69 days, respectively).